Development of local wisdom-based thematic teaching materials to improve adaptive cultural literacy - Gumono Gumono; Sarwit Sarwono; Didi Yulistio; Kholis Abdika Pitawan; Muhammad Solihin; Ecandra Julianto (Community Empowerment, 2022)
This community service was carried out because Indonesian junior high school teachers in Bengkulu City still lacked skills, expertise, and knowledge on how to incorporate culture and local wisdom while creating educational materials. The method chosen was training and mentoring in the development of teaching materials which was attended by 48 Indonesian language teachers from SMP/MTs. The teaching materials developed are in the form of Student Worksheets (LKPD). The outcomes of PkM demonstrate that teachers' understanding of the importance of teaching materials based on local wisdom to enhance adaptive cultural literacy has risen after taking part in a number of activities. Furthermore, there has been a noticeable rise in the ability of Indonesian junior high school teachers in Bengkulu City to create instructional materials for the Indonesian language based on local wisdom. Evidently, over the course of a month, a number of teacher teams were successful in creating LKPD with the primary content drawn from folklore, legends, traditional ceremonies, and cultural objects.